The Impact of Culture, Prior Commitment and Anchoring Effect on preferences for Loyalty Programs - Zizos, Nikolaos (2013)
The first aim of this paper was to examine the impact of culture on customers’ preference towards five different types of loyalty programs. The first lab experiment presented in this thesis tested the preference of students from Brazil, China, Germany, India and Russia towards five different types of loyalty programs offering a low involvement purchase. The loyalty program that offered an immediate reward was the most attractive in all countries, however the level of attraction significantly varied between subjects from different countries. Preference towards direct and indirect rewards was found significantly different among subjects from different countries. In addition, Hofstede’s cultural characteristics: collectivism, power distance, uncertainty avoidance and masculinity were used in order to describe subjects’ behaviour. Masculinity was found negatively related to preference towards immediate rewards and positively related to preference towards non-monetary and direct rewards. Collectivism was found positively related to preference towards indirect rewards whereas uncertainty avoidance was found to be negatively related to behavioural loyalty. The second aim of this paper was to test the influence of prior commitment and anchoring effects in loyalty program preference. The second lab experiment presented in this thesis was conducted in Germany and results showed that prior commitment and information regarding previous participants, increased subjects’ levels of behavioral loyalty. All of the data presented in this study were collected by Professor Thorsten Chmura1 and Dr. Frauke Mattison Thompson2 and they are their property.